Quantitative Endogenous Fluorescence Analysis Discriminates Glioblastoma Tumor through Visible and NIR Excitation - Hussein Mehidine; Emile Kaadou Mouawad; Pascale Varlet; Bertrand Devaux; Darine Abi Haidar (Photonics, 2023)
Nowadays, the ability to diagnose brain tumors intraoperatively and delineate their margins, as accurately as possible, is of primordial importance during surgery. However, the exact tumor boundaries and targets are difficult to find due to the similar visual appearances especially at the margins, leading in many cases to poor surgical outcomes and a high risk of recurrences. To solve this dogma, our group tried to determine different tissue optical signatures such as optical parameters and endogenous fluorescence. For that, we conducted a comparative study to differentiate between healthy and tumorous tissues under one- and two-photon excitations on optical properties to explore several optical parameters. In addition, the study of endogenous fluorescence can successfully help with the discrimination between tissue types using one- and two-photon excitations. This works suggests that the multimodal analysis of optical signatures of tissues could be a reliable technique that can be used to differentiate between healthy and tumorous tissues. This can help in the future with the implementation of such techniques in vivo during surgery to help the surgeon with the decision that needs to be taken as for tissue resection.